2017
DOI: 10.1136/jnnp-2016-314956
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of survival in progressive supranuclear palsy and multiple system atrophy: a systematic review and meta-analysis

Abstract: (2017) Predictors of survival in progressive supranuclear palsy and multiple system atrophy: a systematic review and meta-analysis. Journal of Neurology, Neurosurgery and Psychiatry, 88 (16). This version is available from Sussex Research Online: http://sro.sussex.ac.uk/67644/ This document is made available in accordance with publisher policies and may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 56 publications
11
83
0
Order By: Relevance
“…Dementia, dysphagia and supranuclear gaze palsy have been variably reported to be clinical predictors of death in PSP-RS. 30, 31 In our PSP-F cohort, both dysphagia and supranuclear gaze palsy were over-expressed compared to bvFTD patients, suggesting a possible role of either symptom on survival. However, dysphagia was the only symptom not consistently over-expressed in PSP-SL and PSP-CBS cases.…”
Section: Discussionmentioning
confidence: 77%
“…Dementia, dysphagia and supranuclear gaze palsy have been variably reported to be clinical predictors of death in PSP-RS. 30, 31 In our PSP-F cohort, both dysphagia and supranuclear gaze palsy were over-expressed compared to bvFTD patients, suggesting a possible role of either symptom on survival. However, dysphagia was the only symptom not consistently over-expressed in PSP-SL and PSP-CBS cases.…”
Section: Discussionmentioning
confidence: 77%
“…Indeed, the diagnosis of probable or possible MSA according to the 2008 consensus criteria (Table 1) relies on either the presence of OH or urinary dysfunction indicating pathological involvement of autonomic neurons (Gilman et al, 2008). Early and severe autonomic failure appears to be associated with poorer prognosis (Coon et al, 2015; Glasmacher et al, 2017). Bladder and sexual dysfunction (erectile dysfunction in men and dyspareunia in women) as well as orthostatic dizziness, lightheadedness or syncope due to neurogenic OH were the earliest signs of the disease in up to 50% of patients, years before the emergence of motor signs (Kaufmann et al, 2017b).…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Given that most disabling disorders in PSP are due to balance deficit, walking impairment and falls with related injuries, all studies predominantly focused on these functional domains, in particular balance and gait impairment, apart from one study that addressed voice and speech phonation [26]. Indeed, recent studies have shown that postural instability with early falls, Richardson‐type PSP, and dementia are the main predictive negative factors [32,33]. With regard to balance, all case reports showed an improvement of this functionality with a reduction in falls.…”
Section: Discussionmentioning
confidence: 99%